From Ikhtilaf to Eklektisisme: Tracing Qodri Azizy's Evolutionary Perspectives on Islamic Legal Concepts - Nurdin, Nazar; Ridwan, Ridwan; Widianto, Eko (Media Syari'ah : Wahana Kajian Hukum Islam dan Pranata Sosial, 2024)
This article delves into and elucidates the framework of Qodri Azizy's Islamic legal thought as a prominent Muslim intellectual in Indonesia. His contemplations on eclecticism are deemed crucial in the context of national legal development, emerging from specific situations and contexts. The analysis employs normative and hermeneutical approaches, encompassing significant works such as "Ikhtilaf in Islamic Law" and "Reformasi Bermazhab". The idea of eclecticism in Islamic law is understood through Fazlur Rahman's hermeneutics of the double movement. Qodri's thoughts are influenced by his educational environment in the United States, particularly regarding the concepts of ikhtilaf, madhhab, and talfiq. His critique of scholars who neglect the historical understanding of Islamic law results in a perception of legal opinions as unalterable dogma. Qodri asserts that legal opinions from past scholars result from a dialectical process and interaction of ideas, emphasizing their relative nature. In the modern context, Qodri's views remain relevant as he underscores that legal truth is relative, and a process of mutual enrichment (eclecticism) occurs, where seemingly strong opinions are supported by weaker ones.